The Consumer Protection in The Balance of Business Actors and Consumers: A Paradigm of Justice - Nofrial, Ramon; Abood, Talib Adnan; Shihab, Haider Ahmed; Susilo, Adhi Budi (Jurnal Hukum, 2025)
Consumer protection is a basic need because consumers are in a weaker position compared to business actors, who often pursue profits with business practices that can be detrimental. The aim of this research is to examine consumer protection in realizing a welfare state based on Pancasila, analyze the legal protection against the use of standard clauses, and formulate a legal reconstruction of consumer protection regarding the enforcement of administrative and criminal law in resolving consumer disputes. This research uses a socio-legal research approach. The results of this research are that reconstruction of legal protection for consumers is needed to prevent counterclaims against consumers who report violations. Thus, it is proposed that there be provisions for legal immunity for reporting consumers so that they cannot be prosecuted criminally or civilly before it is proven that the business actor is innocent. The formulation of criminal sanctions in the Consumer Protection Law also needs to be reconstructed so that it is in accordance with the legal system in force in Indonesia. Additional criminal sanctions such as revocation of business permits should not be the authority of criminal courts, but should be part of administrative authority.